Management of failed stainless steel implants in the oromaxillofacial region of dogs - Evenhuis, Janny V.; Verstraete, Frank J. M.; Arzi, Boaz (Frontiers in Veterinary Science, 2022)
Management of complications of fracture fixation in the oromaxillofacial (OMF) region may present a diagnostic and therapeutic challenge. While titanium and stainless steel implants have been utilized in successful fracture fixation in the OMF region, the use of titanium implants is preferred due to the superior intrinsic properties of titanium. Nonetheless, stainless steel materials are still used due to their availability and familiarity of use. In the present method report we describe our approach for the management of failed stainless steel plates and screws used to treat traumatic injuries in the OMF region. Furthermore, we exemplify our approach with five dogs that exhibited complications of stainless steel implants in the OMF region and their subsequent management. In those cases, all failed implants were removed. Reconstruction with a combination of recombinant human bone morphogenetic protein-2 (rhBMP-2) and and titanium implants was utilized in two cases while a mandibulectomy was performed in one case. Three cases required removal of the stainless-steel implant with no additional surgical therapy. We conclude that the success of treatment of failed stainless steel implants depends on the use of advanced imaging findings, appropriate antimicrobial therapy, as well as potentially regenerative reconstructive surgery.